2018
DOI: 10.31580/jmi.v5i1.26
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Oil Price Fluctuations on Industry Stock Returns: Evidence from International Markets

Abstract: This study investigates the impact of oil price variation on 14 industries in six markets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Waheed et al (2018) found direct strong association between oil price changes & stock return (Filis et al, 2011) found strong negative relationship between stock market prices and oil price in case of any non-economic crisis. Tahmoorespour et al (2018) showcased that price volatility of oil, mainly impact the oil & gas industry as well as chronological impact on mining industry but have an insignificant or least effected food & beverage industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Waheed et al (2018) found direct strong association between oil price changes & stock return (Filis et al, 2011) found strong negative relationship between stock market prices and oil price in case of any non-economic crisis. Tahmoorespour et al (2018) showcased that price volatility of oil, mainly impact the oil & gas industry as well as chronological impact on mining industry but have an insignificant or least effected food & beverage industry.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fluctuations in fuel prices have been demonstra ted to impact stock returns in various industries, including the airline and petroleum sectors. Research has indicated that oil price fluctuations predominantly affect the Oil and Gas and Mining industries (Randjbaran et al, 2018). Within the aviation sector, fuel price shocks lead to fluctuations in airline stock returns, with American Airlines, Delta Air Lines, United Airlines, and US Airways showing statistically significant negative relationships between their stock returns and fuel price shocks (Hsu, 2017).…”
Section: The Effect Of Fuel Price Fluctuations On Stock Returnsmentioning
confidence: 99%
“…Questions of statistical analysis of the market indices are the subject of research in the scientific works of both domestic (Almosov et al, 2019;Bobkov and Skorina, 2019;Orlov, 2018;Rusakovich and Malyutina, 2018;Shkarina, 2019;Mikhailov 2018) and foreign experts (Bass, 2017;Marashdeh and Afandi, 2017;Randjbaran, et al, 2018;Waheed, 2018;Ferrera et al, 2019). Some researchers, such as (Orlov, 2018;Bass, 2017), determine that in the near future a significant factor of influence on the oil market development (and then the industry market) should be the formation of a special trade regime for fuel within the WTO.…”
Section: Review Of Literaturementioning
confidence: 99%